The Successful and Safe Real-Time TDM-Guided Treatment of Invasive Pulmonary Aspergillosis Using Isavuconazole Administered by Enteral Tube - Álvaro Corral Alaejos; Jose Jiménez Casaus; Ángel López Delgado; Aranzazu Zarzuelo Castañeda (International Journal of Translational Medicine)
Background: Invasive aspergillosis (IA) is an opportunistic infection that affects immunocompromised patients. While voriconazole is commonly used for IA treatment, it presents the risk of drug interactions, particularly in patients on polytherapy. Isavuconazole may serve as a safer alternative with fewer interactions. However, the use of isavuconazole is typically limited to the parenteral route for patients without access to the enteral route, due to recommendations against tablet handling for enteral administration. The objective of this study was to evaluate the suitability of isavuconazole administration via an enteral tube, by therapeutic drug monitoring of isavuconazole plasma concentrations. Methods: This case study examines a patient with diffuse large B-cell lymphoma who was diagnosed with IA and treated with isavuconazole via an enteral tube. Therapeutic pharmacokinetic monitoring of isavuconazole plasma concentrations was performed to assess the feasibility and safety of enteral administration. Results: The results show that isavuconazole concentrations were maintained within the therapeutic range when administered via an enteral tube. No significant deviations in plasma concentration were noted during the monitoring period. Conclusions: Administering isavuconazole through an enteral tube is a safe and viable alternative for patients that are unable to receive the drug via the oral route. Therapeutic monitoring of plasma concentrations is recommended to ensure proper dosing and efficacy.